POMPA AIR BERTENAGA SURYA SOLUSI UNTUK LAHAN PERTANIAN DI DESA SUKOSARI - Langlang Gumilar; Arif Afandi; Quota Sias; Achmad Fakhri; Arie Muazib; Eka Mistakim; Muhammad Andriansyah (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2022)
Abstract The extent of agricultural land in Sukosari Village makes agriculture the main source of income for most of the Sukosari village community. The extent of agricultural land and limited water supply causes a shortage of water supply in some agricultural lands. This is caused by several things, including the distance from the springs, the dependence of some rice fields on rainwater and the presence of sand miners which aggravate the situation. To solve this problem, the Malang State University (UM) service team utilizes renewable energy in the form of PLTS as a source of electrical energy for water pumps. This solar-powered water pump is used to drain water from a low-lying source to a higher-rise rice field. The PLTS system with a solar powered water pump built has a capacity of 500WP with a 200Ah battery. The energy generated by PLTS will turn on a Shimizu PS 128 Bit water pump. The water produced by the water pump will flow through the rainfed rice fields so that the land becomes productive. With the use of Solar Powered Water Pumps, it is hoped that it can help solve the problem of water shortages, so as to increase the productivity of agricultural land which leads to increasing the income of farmers in Sukosari Village. Abstrak Luasnya lahan pertanian di Desa Sukosari menjadikan pertanian sebagai sumber penghasilan utama oleh sebagian besar masyarakat desa Sukosari. Luasnya lahan pertaniaan dan terbatasnya pasokan air menyebabkan kekurangan pasokan air pada sebagian lahan pertanian. Hal tersebut disebabkan oleh beberapa hal diantaranya yaitu jauhnya sumber mata air, ketergantungan sebagian sawah pada air hujan dan adanya penambang pasir yang memperparah keadaan tersebut. Untuk menyelesaikan permasalahan tersebut, tim pengabdian Universitas Negeri Malang (UM) memanfaatkan renewable energy dalam bentuk PLTS sebagai sumber energi listrik untuk pompa air. Pompa air bertenaga surya ini digunakan untuk mengalirkan air dari sumber yang berada rendah ke sawah yang berada lebih tinggi. Sistem PLTS dengan pompa air bertenaga surya yang dibangun memiliki kapasitas 500WP dengan baterai 200Ah. Energi yang dihasilkan oleh PLTS akan menghidupkan sebuah pompa air Shimizu PS 128 Bit. Air yang dihasilkan oleh pompa air akan mengaliri sawah tadah hujan sehingga lahan menjadi produktif. Dengan pemanfaatan Pompa Air Bertenaga Surya, harapannya dapat membantu menyelesaikan permasalahan kekurangan air, sehingga dapat meningkatkan produktivitas dari lahan pertanian yang berujung pada meningkatkan penghasilan para petani di Desa Sukosari.